Non-Small Cell Lung Carcinoma Biomarker Testing: The Pathologist’s Perspective - Brega, Elisa; Brandao, Guilherme (Frontiers in Oncology, 2014)
Biomarker testing has become standard of care for patients diagnosed with non-small cell lung cancer. Although it can be successfully performed in circulating tu-mor cells, at present, the vast majority of investigations are carried out using di-rect tumor sampling, either through aspiration methods, which render most often isolated cells, or tissue sampling, that could range from minute biopsies to large resections. Consequently, pathologists play a central role in this process. Recent evidence suggests that refining NSCLC diagnosis might be clinically signifi-cant, particularly in cases of lung adenocarcinomas (ADC), which in turn, has prompted a new proposal for the histologic classification of such pulmonary neo-plasms. These changes, in conjunction with the mandatory incorporation of biomarker testing in routine NSCLC tissue processing, have directly affected the pathologist’s role in lung cancer work-up. This new role pathologists must play is complex and demanding, and requires a close interaction with surgeons, oncologists, radiologists and molecular pathologists. Pathologists often find themselves as the central figure in the coordination of a process, that involves assuring that the tumor samples are properly fixed, but without disruption of the DNA structure, obtaining the proper diagnosis with a minimum of tissue waste, providing pre-analytical evaluation of tumor samples selected for biomarker testing, which includes assessment of the proportion of tumor to normal tissues, as well as cell viability, and assuring that this entire pro-cess happens in a timely fashion. Therefore, it is part of the pathologist’s respon-sibilities to assure that the samples received in their laboratories, be processed in a manner that allows for optimal biomarker testing. This article goal is to discuss the essential role pathologists must play NSCLC bi-omarker testing, as well as to provide a summarized review of the main NSCLC bi-omarkers of clinical interest.